2011
DOI: 10.1111/j.1540-8175.2011.01522.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenitally Corrected Transposition of the Great Arteries with Severely Stenotic Bicuspid Aortic Valve in an Adult: A Case Report

Abstract: Congenitally corrected transposition of the great arteries (CCTGA) is a rare disease accounting for 0.5-1.4% of patients with congenital heart disease. In this congenital cardiopathy, the left atrium is connected to the right ventricle, from which the aorta stems. We present a case of an adult with CCTGA associated with aortic stenosis and bicuspid aortic valve-an association not yet described to our knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…A case report of a patient with bicuspid aortic valve who developed AS in the fifth decade of life is consistent with this observation. 8 Second, consideration should be given to epicardial systemic lead placement in all adult patients with ccTGA undergoing open heart surgery. The risk of complete heart block is high, and endovascular systemic lead placement is known to present technical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…A case report of a patient with bicuspid aortic valve who developed AS in the fifth decade of life is consistent with this observation. 8 Second, consideration should be given to epicardial systemic lead placement in all adult patients with ccTGA undergoing open heart surgery. The risk of complete heart block is high, and endovascular systemic lead placement is known to present technical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Fricke et al [11][12][13][14] reported that up to 2% of transposition repair patients need an AVR or SAV, which is not a negligible proportion. Native AoV stenosis with congenitally corrected transposition is rare, described only in case reports [26,27].…”
Section: Transposition Type Complex Congenital Heart Diseasementioning
confidence: 99%
“…Association of bicuspid aortic valve with ccTGA is extremely rare (limited to three prior case reports). [1][2][3] Out of the three reports in the literature, aortic stenosis was present in two patients and regurgitation in one patient. This aortic valve morphology, when present, may require surgical management depending upon the severity of valve stenosis/regurgitation and degree of right ventricular dysfunction.…”
mentioning
confidence: 99%